Measuring the relationship between legal, political environment and freedom of information in Malaysian print media - Kannan Loganathan,; Ali Salman,; Emma Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Previous studies only focused on the media policies and regulations. There is no specific research that has been done to track the freedom of information in print media in Malaysia. This study traces the freedom of information in the print media by exploring and analyzing the relationship between legal environment and political environment and freedom of information. A survey research was conducted to obtain data to determine the level and to analyze the legal and political environment in relation to freedom of information. Descriptive and inferential statistics were used to analyze the data. The study found that the legal and political environment have significant relationship with freedom of information in print media in Malaysia.